Dr. Fausto de Thomas Mann: um romance polifônico dodecafônico - Lourenço, Marise Gândara (2020)
The main objective of this thesis is to analyze the theoretical polyphony in Doctor Faustus, by Thomas Mann, a novel published in 1947. We investigate too the innovative approach towards the technique of the novel, trying to evince how it uses the jargon of musical language and also the coherence of it being an essay-novel, or a Künstlerroman (artist’s novel), among other particularities. We comment The story of a novel, also by Thomas Mann, as a component piece of his polyphonic game, in line with Adorno’s premises in Towards a portrait of Thomas Mann regarding a game of “secrecies” and “hiddenness” in Mann’s writing, capable of taking him beyond the simplistic and reductionist label of ironic author imposed by critics and scholars. In addition, this analysis renders possible to visualize very concretely Doctor Faustus as an “ironic polyphonic” in dialectical basis, highlighting the particular operations of this compositional process in Literature and in literary as written language, a process that is proper to them, distinct from that of musical language. To outline it as effectively and coherently as planned, it is central to highlight the irrelevant and innocuous act of transmuting Literature in Music, constantly performed by a number of critics and scholars in Letters, Literature and Linguistic Studies. Our approach dialogues with one hypothesis: if Bakhtin proposes the terms polyphonic novel while creating his theory on Dostoevsky, and justifies it as a mere analogy, a figurative metaphor, rendering quite evidently his carefulness not to debase literary art in its equivocate transmutation of in Music; if he does so, Thomas Mann establishes the polyphony as something so natural to Literature and literary as written language as it is to Music and musical language. He does so through his theoretical polyphonic in Dr. Faustus. Lastly we mention the conference-essay A arte do romance, by Mann, text of fundamental importance. It consists in a rich and solid critic of the construction of human knowledge, guiding us to our conception of art, among other ideas and concepts. Besides that we declare that our academic outline is constituted by two intertwined thesis and that it is characterized by the involvement with diverse areas of knowledge: Literature, Music, Neuroscience, Musical Acoustics e Philosophy.